2015
DOI: 10.1016/j.jmmm.2015.05.084
|View full text |Cite
|
Sign up to set email alerts
|

Memory effect versus exchange bias for maghemite nanoparticles

Abstract: a b s t r a c tWe studied the temperature dependence of memory and exchange bias effects and their dependence on each other in maghemite (γ-Fe 2 O 3 ) nanoparticles by using magnetization studies. Memory effect in zero field cooled process in nanoparticles is a fingerprint of spin-glass behavior which can be due to i) surface disordered spins (surface spin-glass) and/or ii) randomly frozen and interacting nanoparticles core spins (super spin-glass). Temperature region (25-70 K) for measurements has been chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
5
2
Order By: Relevance
“…However, from careful repeated experiments, we confirmed that ZFC MME is absent in the MND sample. The observed results differ significantly from the literature in which both FC and ZFC MME were reported from γ-Fe 2 O 3 and Fe/γ-Fe 2 O 3 nanostructure, confirming SG state [ 4 , 5 , 23 ]. However, the obtained MME from MND partially agrees with weakly interacting γ-Fe 2 O 3 -alginate nanocomposite from which only FC MME (but with decreasing magnetization) without ZFC MME was reported in the low-temperature region far below RT [ 6 ].…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, from careful repeated experiments, we confirmed that ZFC MME is absent in the MND sample. The observed results differ significantly from the literature in which both FC and ZFC MME were reported from γ-Fe 2 O 3 and Fe/γ-Fe 2 O 3 nanostructure, confirming SG state [ 4 , 5 , 23 ]. However, the obtained MME from MND partially agrees with weakly interacting γ-Fe 2 O 3 -alginate nanocomposite from which only FC MME (but with decreasing magnetization) without ZFC MME was reported in the low-temperature region far below RT [ 6 ].…”
Section: Resultscontrasting
confidence: 99%
“…The FC M(H a ) loop exhibits a loop shift in either direction depending on the direction of the cooling field with a similar EB field H EB of 11 Oe. The obtained value of the H EB is much smaller than the reported value of around 77 Oe under a cooling field of 50 kOe from 6.1 nm SG like γ-Fe 2 O 3 nanoparticles [ 23 ]. The origin of a relatively small EB field from the MND sample possibly lies at the interfacial spin-exchange interaction between vacancy-induced short-range magnetic clusters and compensated ferrimagnetic γ-Fe 2 O 3 .…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…In addition to intrinsic spin disorder and frustration in magnetic materials, the interfacial magnetic exchange interactions in hetero-structured systems have shown many novel magnetic phenomena, e.g., blocking of magnetic domains, domain wall pinning, exchange bias, training effect, and memory effect [6][7][8][9][10][11][12][13]. The exchange bias effect was primarily modeled for FM and AFM layers of thin films [3][4].…”
Section: Introductionmentioning
confidence: 99%